O ENSINO DE CIÊNCIAS E DE QUÍMICA NO ENSINO FUNDAMENTAL (Revista Eletrônica Debates em Educação Científica e Tecnológica, 2021)
The teaching of Chemistry is generally represented in the last year of Elementary School (ES), as the teaching of Physics, as introduction to enter High School. In relation to this, the option was to make the review based on Meeting of Debates on Teaching Chemistry congress annals and by the search for master thesis in the databank from CAPES, from 2012 to 2014, it was aiming at observing how chemistry teaching is taught in ES. Some limitations emerge (lack of time and excessive use of textbook) as well as some possibilities (continuing formation, study groups, research and Study Situations) to effective the teaching of Chemistry in the ES, concluding with the approach of reconnection of knowledge demarcates the curricular reorganization from the 6th to 9th degree of ES.
Keywords: Science Teaching; Curricular Reorganization; Teaching and Learning